Book Review: Radical right populism in Germany: AfD, pegida, and the identitarian movement - Hansen Michael A. (SAGE Publications, 2022)
Havertz Ralf . Abingdon, Oxon and New York, NY. Routledge Press, 2021; pp.:ISBN: 9780367372026, £96.00 (bbk) £27.99 (pbk, ebook)